Profil dan Kompetensi Guru Bahasa Arab Madrasah Aliyah Negeri di Bangka Belitung - Syarifah, Syarifah; Iskandi, Iskandi (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
This article aims to describe the profile of Madrasah Aliyah Negeri Arabic Language Teachers in the Bangka Belitung Islands Province, the relevance of the academic qualifications of Arabic Language Teachers with Subjects taught in Madrasah Aliyah Negeri, and the competence of Arabic Language Teachers in terms of students' perspectives. The research method used is descriptive quantitative, with data collection techniques such as questionnaires and documentation. The results showed that when viewed from academic qualifications, Arabic teachers who already have PBA S1 academic qualifications had a percentage of 80% and other S1 academic qualifications of 20%. Referring to these data, the relevance of Arabic language science to subjects taught based on academic qualifications is 80:20. Whereas if the scientific relevance is reviewed from the professional certificate, Arabic teachers who have professional certificates as professional Arabic teachers are 60% and those that have not been certified are 40%. Based on students' perspectives, the competence of Arabic language teachers in Madrasah Aliyah Negeri Bangka Belitung Islands Province is as follows: Pedagogical Competence with a mean score of 2.64, Professional Competence of 3.00, Social Competence of 3.03, and Personality Competence of 3.04. The overall average score of the four competencies is 2.99 with the interpretation